THE DEBT MANAGEMENT PATTERNS OF EDUCATIONAL LOAN RECIPIENTS AMONG POLYTECHNIC STUDENTS IN KOTA KINABALU, SABAH: AN EMPIRICAL STUDY - Hainnur Aqma Rahim; Ngau Duo Seng; Dicky Wiwittan Toto Ngadiman; Nor Asmat Ismail (International Journal of Accounting, Finance and Business, 2020)
There has been an increase in the number of students registering in higher learning institutions, but there is a big gap between the number of graduates and the number of scholarships provided. Following that, the cost of education at both public and private higher learning institutes is on the increase day by day. Other than having to spend money on learning purposes like academic materials, stationery and so on, students are also affected by the increased price of necessities, like food and others. This is because, they only depend on the scholarship, loan or financial assistance given by their parents. With this in mind, this study seeks to investigate students' habit when it comes to managing their educational loans. Based on the random sampling method, 352 students from the Polytechnic in Kota Kinabalu, Sabah (PKK) comprising of Sabah Bumiputera (66.5%), Sarawak Bumiputera (3.5%), Malay (14.1%), Chinese (4.1%), Indian (1.2%) and others (10.6%) were selected. The study finds that although the students have received their loans, they are still having the financial burden due to the parents' lack of financial stability. Thus, students must be equipped with financial management knowledge so that any financial problems they face can be addressed.